Establishing a Filipino mother tongue program in Reykjavík : an action research project - Kriselle Lou Suson Cagatin 1988- (2013)
Numerous studies verify the importance of bilingual children’s mother tongue in their overall development. This research project investigates the establishment of an efficient mother tongue program for Filipinos in Reykjavík, Iceland, which began in spring, 2011 only to stop for a year and recommence in autumn 2012. Philippine-born immigrants made up the largest Asian minority group in Iceland in early 2012, which signifies a huge target group for the program. The study briefly examines: the language environment of Icelandic children who have Filipino immigrant parents, parents’ views on their children’s bilingualism, teacher’s views on the mother tongue program; and organizational strategies for confronting the subsequent challenges and looking into the courses of action within the organization and implementation processes. It came to light that about 80% of the students were Filipino language beginners with Icelandic as their mother tongue, thus teaching Filipino as a second language came to be more appropriate for most students. As a consequence, additional network of Filipino teachers was needed. Incidentally, motivating and educating parents about the importance of their mother tongue also appeared to be essential. Therefore based on the complexity of these circumstances, it became better to formally establish the Filipino Mother Tongue Organization, “Inangwika: Filippseyskt móðurmálsfélagið” to accomplish necessary actions for this target group.